Permainan Ular Tangga Dengan Penguatan Self Esteem Dapat Meningkatkan Kepercayaan Diri Penyandang Disabilitas Di Yayasan Bhakti Senang Hati - Parwati, Ni Putu Yuniarika; Meriani, Ega Dwi; Udiani, Made Dwi; Nufus, Ziadatun; Rukka, Hestika Angelina; Zaini, Adjie Achmad (Journal Prakarsa Paedagogia, 2025)
This study aims to improve the self-confidence of persons with disabilities through an educational snakes and ladders game integrated with self-esteem reinforcement. Using an action research method in two cycles, the study was conducted within the Bhakti Senang Hati Foundation community. The results showed a significant increase in self-confidence, from 68.8% in the pre-cycle to 74.5% in the second cycle. This improvement was achieved through a game designed to stimulate social interaction, public speaking courage, and self-expression. The novelty of this research lies in the integration of traditional games with a psychological approach based on self-esteem enhancement within the context of empowering people with disabilities. In conclusion, the snakes and ladders game combined with self-esteem reinforcement proved to be an effective and enjoyable strategy to enhance self-confidence among persons with disabilities, and it can be considered an alternative method for psychosocial community interventions.